2021
DOI: 10.18632/aging.202906
|View full text |Cite
|
Sign up to set email alerts
|

Mendelian randomization as an approach to assess causal effects of inflammatory bowel disease on atrial fibrillation

Abstract: Background: Despite growing evidence indicating that patients with inflammatory bowel disease (IBD) have an increased risk of atrial fibrillation (AF), owing to the potential biases of confounding effects and reverse causation, the specific relationship between IBD and AF remains controversial. The aim of this study is to determine whether there is a causal effect of IBD on AF. Methods: A two-sample Mendelian randomization (MR) study was performed to evaluate the causal effect of IBD on AF. Statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 49 publications
(56 reference statements)
1
5
0
Order By: Relevance
“…Thus, we speculated that IBD patients have increased levels of traditional cardiovascular risk factors, resulting in an increased incidence of CVD in observational studies. Recent MR studies showed a lack of genetic causality between IBD and atrial fibrillation (42), which was consistent with our results. Although pleiotropy may cause the bias of the results in MR analysis, there is little possibility in our study (43).…”
Section: Discussionsupporting
confidence: 93%
“…Thus, we speculated that IBD patients have increased levels of traditional cardiovascular risk factors, resulting in an increased incidence of CVD in observational studies. Recent MR studies showed a lack of genetic causality between IBD and atrial fibrillation (42), which was consistent with our results. Although pleiotropy may cause the bias of the results in MR analysis, there is little possibility in our study (43).…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we concentrated on the interactive effects between the gut microbiome and GD through bidirectional MR analysis, which we also used to detect the causal effect between the gut microbiome and GD. Compared with traditional clinical trials, MR analysis allows the identification of sequential relationships as the exposure is defined before the outcome through IVs in the design of the MR analysis, and IVs are less prone to influence by potential confounders ( 49 ). The present study utilized F -statistics and horizontal pleiotropy, which overcame weak biases and showed a direct association between SNPs and the outcome.…”
Section: Discussionmentioning
confidence: 99%
“…in PA and minimizing sedentary time are linked to decreased weight gain and body fat, while overweight is associated with an increased risk of frailty and falls. [53][54][55] Given that body fat is likely involved in the causal pathway linking PA, sedentary behavior, and frailty and falling, it is challenging to disentangle independent effects of PA and sedentary behavior on the development of frailty and falling from adiposity. The close association between adiposity, PA, and sedentary behavior could be attributed to the fact that certain genetic instruments used to measure PA and LST have also demonstrated associations with genotypes associated with body fat.…”
Section: Discussionmentioning
confidence: 99%
“…Engaging in PA and minimizing sedentary time are linked to decreased weight gain and body fat, while overweight is associated with an increased risk of frailty and falls 53–55 . Given that body fat is likely involved in the causal pathway linking PA, sedentary behavior, and frailty and falling, it is challenging to disentangle independent effects of PA and sedentary behavior on the development of frailty and falling from adiposity.…”
Section: Discussionmentioning
confidence: 99%